ChemInform Abstract: ZnO Nanoparticles as Reusable Heterogeneous Catalyst for Efficient one Pot Three Component Synthesis of Imidazo‐Fused Polyheterocycles. Issue 29 (29th June 2016) - Swami, Suman; Devi, Nisha; Agarwala, Arunava; Singh, Virender; Shrivastava, Rahul
Abstract: A new efficient isocyanide based method to synthesize biologically relevant pyrazole coupled imidazo[1, 2‐a]pyridine derivatives is presented.